2022
DOI: 10.1093/ajcn/nqac266
|View full text |Cite
|
Sign up to set email alerts
|

Infant consumption of microRNA miR-375 in human milk lipids is associated with protection from atopy

Abstract: Background Human milk is thought to reduce infant atopy risk. The biologic mechanism for this protective effect is not fully understood. Objectives We tested the hypothesis that infant consumption of four microRNAs (miR-146b-5p, miR-148b-3p, miR-21–5p, and miR-375–3p) in human milk would be associated with reduced atopy risk. Design The Breast Milk IMPACT Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
(117 reference statements)
1
7
0
Order By: Relevance
“…Intriguingly, miR-22-5p levels appear to potentiate the protective effect of sustained breastfeeding. This is consistent with prior studies suggesting that maternal-infant transfer of miRNAs in breastmilk may impact immune development [ 39 ]. It also supports prior studies implicating miR-22 expression in upper respiratory infections, pneumonia, and asthma [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Intriguingly, miR-22-5p levels appear to potentiate the protective effect of sustained breastfeeding. This is consistent with prior studies suggesting that maternal-infant transfer of miRNAs in breastmilk may impact immune development [ 39 ]. It also supports prior studies implicating miR-22 expression in upper respiratory infections, pneumonia, and asthma [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…This study involved a subset of infants from a prospective longitudinal cohort of 221 mother-infant dyads [ 39 ]. Eligibility criteria were term delivery (37–42 weeks gestation) and plan to breastfeed ≥ four months.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Hicks et al. ( 16 ) recently showed that breast milk miR-375 seem to decrease the risk of atopy in breastfed infants; a miRNA that did not make it on to our top 10 list. Nevertheless, while acknowledging this as a potential shortcoming, we believe that adhering to a systematic approach in selecting which miRNAs to focus on adds rigor to this review.…”
Section: Discussionmentioning
confidence: 78%
“…Although the biological relevance remains to be clarified, this conservation of sequence suggest that miRNAs serve fundamental functions. Like other breast milk components, the miRNA profile seems to vary over time, displaying daily as well as more long-term fluctuations ( 14 , 16 , 17 ), although empirical data is still scarce. An astonishing >1,900 different types of miRNAs have been detected in human breast milk, with potential biological implications on cell communication, fatty acid biosynthesis, regulation of actin skeleton and a vast number of immunological pathways ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…This study involved a secondary analysis of data collected as part of the Breast Milk IMPACT (Influence of the Micro-transcriptome Profile on Atopy in Children over Time) Study [ 28 ]. The Breast Milk IMPACT study involved a convenience sample of 221 breastfeeding infants enrolled within 7 days of delivery and followed until 12 months of age.…”
Section: Methodsmentioning
confidence: 99%